Does Long-Term Use of Silver Nanoparticles Have Persistent Inhibitory Effect on H. pylori Based on Mongolian Gerbil's Model?. (17th April 2014) - Kuo, Chao-Hung; Lu, Chien-Yu; Yang, Yuan-Chieh; Chin, Chieh; Weng, Bi-Chuang; Liu, Chung-Jung; Chen, Yen-Hsu; Chang, Lin-Li; Kuo, Fu-Chen; Wu, Deng-Chyang; Su, Hong-Lin
Abstract : Background . It is urgent to find alternative agents due to increasing failure rate of Helicobacter pylori (H. pylori ) eradication. The study surveyed the long-term effect of silver nanoparticles (AgNP) on H. pylori based on Mongolian gerbil's model. Materials and Methods . Fifty gerbils were randomly allocated to six groups (A–F). Group (Gr) A: the gerbils were fed with broth; Gr B and D: the gerbils were fed with AgNP/clay complex (0.1% of weight); Gr C and E: the gerbils were fed with AgNP/clay complex(1% of weight); and Gr D, E, and F: the gerbils were inoculated with H. pylori . At the 20th experimental week, the gerbils were sacrificed. Histology was evaluated according to the classification of the Sydney system. P < 0.05 was considered to be statistically significant. Results . The AgNP/clay has more obvious inhibitory effect on H. pylori in vitro. There was a trend of higher concentrations of AgNP with stronger inhibitory effect on H. pylori growth ( P = 0.071 ) . There were no significant differences of inflammation among groups D, E, and F ( P = 0.688 ) . Conclusion . AgNP/clay would be a potential and safe agent for inhibiting H. pylori . It should be helpful for eradication of H. pylori infection.